Delay adaptation does not transfer between discrete button press actions and continuous control - Loes CJ van Dam; Svenja Kernig; Karina Lazarova; Melisa Ünal; Nicole Gappa; Benjamin Straube; Thomas SA Wallis (i-Perception)
When interacting with technology, humans often deal with delays between an action and the desired action outcome. Through delay adaptation these delays will become less detrimental to visuomotor performance over time. Delay adaptation has been shown for a variety of tasks and control modes, from simple button presses causing a beep or flash to continuous target-tracking tasks. Here we investigated whether the delay adaptation is specific for the control mode used, when the task itself remained unaltered. To this end, participants performed a target tracking task in which they controlled a cursor item either by moving a stylus on a graphics tablet or by pressing the arrow keys on a keyboard. We found that delay adaptation occurred for both these types of control modes, but observed no transfer to the other control mode. This indicates that delay adaptation is specific to the control mode used during adaptation.